Identification and characterization of the donkey CSN1S2 I and II cDNAs - Davide Nicodemo; Dino Di Berardino; Lina Chianese; Gabriella Iannolino; Donata Marletta; Luigi Ramunno; Andrea Rando; Annarosaria Lidia Annunziata; Gianfranco Cosenza; Alfredo Pauciullo (Italian Journal of Animal Science, 2010)
The αs2 casein, encoded by the CSN1S2 gene, is one of the three Calcium sensitive caseins present in the milk of ruminants of zootechnical interest and in the milk of Equidae species (horse and donkey). In the present study, we cloned, sequenced and analysed two different donkey CSN1S2 cDNAs that we called CSN1S2 I and CSN1S2 II. The first, which spans over a fragment of 1016 nt, is constituted by 19 exons and encodes for a predicted protein (called αs2-I) of 221 aminoacids; the second, of which we determined the entire sequence (16 exons), encodes for a predicted peptide (called αs2-II) of 168 aminoacids. Alternative splicing and genetic markers are reported for both genes.